Investigasi Kemampuan Justifikasi Siswa dengan Gaya Belajar Diverger dalam Menyelesaikan Soal Cerita Pola Bilangan - Nanda Dwi Yanto; Rofiki, Imam (MATHEdunesa, 2025)
Justification is done to strengthen statements or refute false statements. Students' ability to make justifications is important in solving story problems because it can ensure the correctness or incorrectness of students' answers. However, currently, there are still many students who have difficulty in justifying number pattern story problems. In fact, number patterns are very important for students to master. Therefore, this study aims to investigate the justification ability of students with diverger learning styles in solving number pattern story problem. This research is descriptive research with a qualitative approach. The subjects were selected using a purposive sampling technique so that two students with diverger learning styles were obtained. The research took place at SMPN 1 Plosoklaten. The research instruments consisted of learning-style questionnaires, justification task sheets, and interview guidelines. The results showed that the level of ability of students with diverger learning styles in making justification in solving number pattern story problems is at the deductive justification level. Students give reasons for the solution steps that have been made. In addition, students explain each stage of solving story problems with reasons that are in accordance with student knowledge.